Modification of purified proteins with photochemical protection compounds for high-resolution photoactivation of protein function in vitro and in vivo - Cambridge, Sidney (Photoswitching Proteins, 2014)
Specific and targeted photoactivation of protein function inside cells, tissues, or whole organisms can be achieved with reversible inhibition of proteins by conjugation with photolabile protection compounds ("caging"). In vitro caging of proteins is thought to cause sterical or functional hindrance of amino acid side chains that are important for protein activity. Following the modification, the caged protein is introduced into the biological system and high-resolution irradiation ensures specific release of protein function in the desired areas. Here, I describe the entire caging procedure and highlight a few of the caveats of photoactivation in living cells.